Migratory movements in the international scenario: The plurality of Brazilian immigration policy (1946-1954) - Dos Santos, Amanda Pereira [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2021)
This article examines some aspects of the agreements signed between the Brazilian government and two international organizations, which exercised control over international migratory movements after the Second World War: the International Refugee Organization and the Intergovernmental Committee for European Migration. The establishment of the international regime on refugees proceeded from the mutual interests expressed by western states, which aimed at international cooperation to direct migratory flows. It is argued that Brazilian foreign policy guidelines continued to be aligned with the Western Bloc in the context of the Cold War, which led to the reception of refugees who had fled European countries during and after the end of World War II. The entry of these people into the country met the demand for labor in the agricultural and industrial sectors, which were developing on a large scale. On the other hand, it is noteworthy that the rules for the entry of refugees and immigrants into Brazil were characterized as selective and sought to prevent the immigration of “undesirable elements”, based on ethnic, economic, political-ideological, and moral justifications.
Movimentos migratórios no cenário internacional: A pluralidade da política imigratória Brasileira (1946-1954)
Keywords: Immigration policy; Intergovernmental committee on european migration; International refugee organization